A southward range extension of a wreckfish, Stereolepis doederleini (Actinopterygii: Acropomatiformes: Polyprionidae), to tropical water off eastern Taiwan - Hsuan-Ching Ho (Pensoft Publishers, 2021)
A wreckfish, Stereolepis doederleini Lindberg et Krasyukova, 1969, inhabits typical cold or temperate waters and was previously known from Great Bay (Sea of Japan), Korea, south to Kyuhu-Palau Ridge of Japan. In the present report, a specimen of this fish was collected from southeastern Taiwan representing the southernmost distribution of the cold-water genus Stereolepis in the Northern Hemisphere, with a southward extension into the tropical region. It is also the first record of a member of the family Polyprionidae from Taiwan. Here we document the species found in Taiwan, with a detailed description of the specimen.